Role of Anesthesia Nurses in Managing Sedation and Pain Control in ICU Settings - Meraj, Shazia; Shaukat, Ibtesam; Hussain, Agha Sajjad (Biological and Clinical Sciences Research Journal, 2025)
Sedation and pain management are crucial in ICU care, particularly for critically ill and mechanically ventilated patients. Effective sedation ensures patient comfort, prevents agitation, and facilitates ventilation, while optimal pain control reduces stress responses and improves overall outcomes. In resource-limited healthcare settings such as Pakistan, the role of anaesthesia nurses in managing sedation and pain control remains underexplored. This study evaluates the effectiveness of anaesthesia nurse-led sedation and pain management in ICU patients compared to standard ICU protocols. Methods: This prospective observational study was conducted at a tertiary care hospital over six months (March 2024 to September 2024). A total of 90 ICU patients requiring sedation and pain control were enrolled using non-probability consecutive sampling and divided into two groups: the intervention group (managed by anaesthesia nurses) and the control group (managed under standard ICU protocols). Sedation was assessed using the Richmond Agitation-Sedation Scale (RASS), and pain control was evaluated using the Numeric Pain Rating Scale (NPRS). Primary outcomes included optimal sedation (RASS -2 to 0) and adequate pain control (NPRS ≤3). Secondary outcomes included ICU length of stay, the need for additional analgesia, and sedation-related complications. Statistical analysis was performed using SPSS version 26, with a p-value <0.05 considered statistically significant. Results: The intervention group demonstrated significantly higher rates of optimal sedation (71.1% vs. 53.3%, p = 0.03) and better pain control (84.4% vs. 62.2%, p = 0.02) than the control group. The need for additional analgesia was lower in the intervention group (17.8% vs. 35.6%, p = 0.03). Patients under anaesthesia nurse-led sedation had shorter ICU stays, with 68.9% discharged within five days compared to 46.7% in the control group (p = 0.02). Sedation-related complications, including delirium and hypotension, were significantly lower in the intervention group (6.7% vs. 20.0%, p = 0.04). Conclusion: Anesthesia nurse-led sedation and pain management significantly improve patient outcomes in ICU settings. Patients managed under structured anaesthesia nurse protocols achieve better sedation, more effective pain relief, shorter ICU stays, and fewer complications. These findings support the integration of anaesthesia nurses into ICU care teams in resource-limited settings like Pakistan. Future studies should focus on large-scale, multicenter trials to establish standardised nurse-led sedation and analgesia protocols.